Taxonomic Measurement of Regional Diversification of The Level of Innovation In Poland - Joanna M. SZAREK-ORLECKA (Communications of International Proceedings, 2025)
In the era of exponential development of the digital economy, both globally and regionally, it is crucial to analyze the degree of sophistication of regions in adapting to new economic challenges. The purpose of the study was to show the regional variation in Poland in the level of innovation and the R&D sector, using selected taxonomic methods. With regard to the stated goal, a research hypothesis was formulated: the Mazowieckie voivodeship is the most economically innovative region in Poland. By creating a ranking of provinces according to the standardized sum index, it was possible to identify the dominant group of provinces in Poland in terms of six diagnostic variables. This group included the Mazowieckie Voivodeship and the Silesian Voivodeship.
Keywords: Digital Economy; Knowledge Based Economy; Measurement Regional Diversification.